PREDICTION OF THE COMPONENTS MASS RATIOS AND THE SPECTRAL CLASSES OF THE MAIN COMPONENT FOR W UMa-TYPE ECLIPSING VARIABLE STARS - Svirskaya, E. M.; Shmelev, A. Yu. (Одеські астрономічні публікації, 2017)
The new approach to estimation of components mass ratios for close binary systems is suggested. 225 unknown from spectroscopic observations magnitudes of mass ratios for W UMa-type contact binaries are restored by statistical method ZET. 204 magnitudes of the spectral classes of the main component for this type systems are defined by analogous way. The evolutionary types of some stars are specified as a matter of record. ZET-method efficiency for predict these characteristics of W UMa-type contact systems is shown.